Application of Electronic Means in Endurance Coordination Testing of Students with Disabilities Who are War Veterans - Oksana Blavt; Alina Bodnar; Аnatolii Mykhalskyi; Tetyana Gurtova; Larisa Tsovkh (OVS LLC, 2023)
The purpose of the study was to determine the effectiveness of the use of electronic means created based on information and communication technologies in coordination testing of the endurance of students with disabilities who are war veterans in practical physical education classes. Materials and methods. To solve research problems, scientific intelligence applied the implementation of research at the theoretical and empirical levels. Analysis, synthesis, generalization, induction, systematization, pedagogical experiment, methods of mathematical statistics and technical modeling were used. The study involved 46 students who are war veterans (males aged 17-18). Results. An electronic mean for determining coordination endurance based on information and communication technologies and software has been developed. The design of the mean involves the use of mobile and stationary measuring units and a personal computer. The measuring unit contains analog and digital sensors. Information about the student's performance on the test is displayed on the personal computer screen. Approbation of the developed mean involved establishing the degree of its authenticity by comparing the results of testing the coordination endurance of students with disabilities who are war veterans implemented using traditional methods of measurement and the results of testing using the developed mean. The calculation of the reliability and validity of the tests showed that the recording of control results by electronic means allows ensuring a high level of authenticity of the tests. Conclusions. The use of the electronic control means of coordination endurance presented in the work allows the achievement of a high level of reliability of control results in real time. Based on the summaries of the conducted empirical research, it was established that the introduction of electronic means of control in the process of physical education of students with disabilities who are war veterans helps to ensure the effectiveness of this process.